Improving IT infrastructures representation: A UML profile - Silva, L. F. da. (2012)
IT infrastructures are most times informally modeled. The resulting models are ambiguous to stakeholders, cannot be checked for validity, and therefore are unable to play their important role in design, deployment and maintenance activities. The main reason for such a poor state-of-the-art lies mainly in the absence of a modeling language capable of representing IT infrastructures at the required level of abstraction. Indeed, existing candidate languages are too abstract, as shown in this paper by reviewing their metamodels. The present paper mitigates this problem by proposing a UML profile to describe the semantics of an IT infrastructure.